2011
DOI: 10.1186/cc10047
|View full text |Cite
|
Sign up to set email alerts
|

Real-time ultrasound-guided percutaneous dilatational tracheostomy: a feasibility study

Abstract: IntroductionUltrasound (US) performed prior to percutaneous tracheostomy (PT) may be useful in avoiding injury to pretracheal vascular structures and in avoiding high placement of the tube. Bedside real-time US guidance with visualization of needle path is routinely utilized for other procedures such as central venous catheterization, and may enhance the safety and accuracy of PT without causing airway occlusion or hypercarbia. Our objective was to demonstrate that PT performed under real-time US guidance with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(119 citation statements)
references
References 32 publications
4
111
0
4
Order By: Relevance
“…9 Recently, Rajajee et al demonstrated the feasibility of US guidance during the implementation of PCT in a population of neuro-intensive care patients. 10 USPCT has many potential advantages over other techniques of PCT. The first is the ability to consistently place the tracheostomy tube below the first tracheal ring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Recently, Rajajee et al demonstrated the feasibility of US guidance during the implementation of PCT in a population of neuro-intensive care patients. 10 USPCT has many potential advantages over other techniques of PCT. The first is the ability to consistently place the tracheostomy tube below the first tracheal ring.…”
Section: Discussionmentioning
confidence: 99%
“…Placement of the tracheal tube above the first tracheal ring may increase the risk of late sub-glottic cicatrization and stenosis. 7,9,10 In one study of patients who underwent autopsy following PCT, 5 of 15 patients had the tracheal tube placed above the first tracheal ring when the tube was placed blindly vs zero of 11 patients when PT was performed with ultrasound guidance.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ultrasound in PT can be advantageous especially in select patient groups, such as those who are morbidly obese or have difficult neck anatomy (68)(69)(70). Bedside ultrasound screening allows for easy identification of pretracheal vascular structures that might pose a hemorrhage risk during PT (71).…”
Section: Role Of Ultrasound In Ptmentioning
confidence: 99%
“…There was no case of tube misplacement, pneumothorax, posterior wall injury, significant bleeding, or other complications. 96 Although ultrasound may not be required in all patients undergoing PDT, real-time ultrasound should be considered in obese patients in whom surface landmarks are difficult to discern, in patients with altered cervical anatomy, and for difficult tracheostomy procedures such as repeat tracheostomy. 97 Another prospective study of 50 consecutive subjects in 2 surgical and critical care medicine departments in France demonstrated that ultrasound-guided percutaneous tracheostomy was feasible and safe in obese patients (median body mass index of 34 kg/m 2 , range of 32-38) with a low complication rate.…”
Section: Prerequisites For Tracheostomy Decannulation In Adult Patientsmentioning
confidence: 99%